2015
DOI: 10.1186/s40657-015-0031-0
|View full text |Cite
|
Sign up to set email alerts
|

Brightness of melanin-based plumage coloration is a cue to oxidative stress in Himalayan Black Bulbuls (Hypsipetes leucocephalus nigerrimus)

Abstract: Background: Melanin-based coloration is often found to be associated with variations in physiological and behavioral traits that are essential in avian communication. However, the function of melanin-based traits to their bearers has been investigated less than that of carotenoid-based ones. It is commonly believed that expression of melanin-based pigmentation is genetically controlled. However, whether it could be modulated by physical condition has remained controversial. In this study, we demonstrate that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Heritable color morphs often have distinct behaviors and physiology, with associated differences in selection pressures on an otherwise common genetic background (Sinervo and Lively, 1996;Pryke and Griffith, 2006;Healey et al, 2007;Pryke et al, 2007;Olsson et al, 2009aOlsson et al, , 2007areviewed in Huxley, 1955;Wellenreuther et al, 2014). Colorful traits often fade during the breeding season, which suggests these traits may have condition-dependent expression and costly to maintain (Cotton et al, 2004;Grunst et al, 2014;Reinhart et al, 2015), which are potentially mediated by oxidative stress (von Schantz et al, 1999;Monaghan et al, 2009;Hõrak et al, 2010;Garratt and Brooks, 2012;Costantini, 2014;Hung and Li, 2015) and body condition (Slagsvold and Lifjeld, 1992;Costantini, 2008;Stephen Dobson et al, 2008). Reactive oxygen species (ROS) damage DNA, proteins and cell membranes, triggering cell death and color-fading (Dowling and Simmons, 2009;Costantini, 2010;Olsson et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Heritable color morphs often have distinct behaviors and physiology, with associated differences in selection pressures on an otherwise common genetic background (Sinervo and Lively, 1996;Pryke and Griffith, 2006;Healey et al, 2007;Pryke et al, 2007;Olsson et al, 2009aOlsson et al, , 2007areviewed in Huxley, 1955;Wellenreuther et al, 2014). Colorful traits often fade during the breeding season, which suggests these traits may have condition-dependent expression and costly to maintain (Cotton et al, 2004;Grunst et al, 2014;Reinhart et al, 2015), which are potentially mediated by oxidative stress (von Schantz et al, 1999;Monaghan et al, 2009;Hõrak et al, 2010;Garratt and Brooks, 2012;Costantini, 2014;Hung and Li, 2015) and body condition (Slagsvold and Lifjeld, 1992;Costantini, 2008;Stephen Dobson et al, 2008). Reactive oxygen species (ROS) damage DNA, proteins and cell membranes, triggering cell death and color-fading (Dowling and Simmons, 2009;Costantini, 2010;Olsson et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that females may choose mates based on multiple sexual ornaments4849; multiple ornaments provide females with diverse information at different stages of mate choice50, or function as redundant signals to improve the accuracy of mate assessment5152. Our data shows that both carotenoid- and melanin-based characteristics are sexually dichromatic in Himalayan black bulbuls, and both could convey information about an individuals’ physical conditions53, [unpublished]. We here propose that in our species, individuals may use multiple cues in sexual selection.…”
Section: Discussionmentioning
confidence: 73%
“…The detailed program set-up of the polymerase chain reactions (PCRs) for molecular sex typing59 was the same as in Hung and Li53. In total, 55 male and 57 female live bulbuls were identified.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Melanin bounds many compounds and retains them for long periods of time. Therefore, melanin‐based pigmentation could be used to assess long‐term physical condition of the individual (Hung & Li, 2015). Melanin coloration results from the co‐occurrence of both eumelanin and pheomelanin pigments at different concentrations (McGraw & Parker, 2006; Zduniak et al., 2014).…”
Section: Resultsmentioning
confidence: 99%